Fundamentals of political science - Ayson, Florentino G.; Reyes, Dolores A. (Mandaluyong City, Philippines : National Book Store, 1993)
Political Science is the study of state in all its elements, aspects, and relationships. a systematic study of politics, an attempt by systematic analysis to discover in the confusing detail whatever principles may exist of wider and more general significance.
CHAPTER 1. The Nature and scope of Political Science -- 2. The meaning and nature of the state -- 3. The classifications of Government -- 4. The Constitution -- 5. The Rule of Law -- 6. Citizenship -- 7. Suffrage and the electoral process -- 8. Political parties and Personal organizations -- 9. Pressure groups and their role in a democratic society -- 10. Public Opinion and Propaganda --11. The Legislature -- 12. The executive -- 13. The Judiciary -- 14. The meaning and nature of Bureaucracy -- 15. Local Government -- 16. Relations Among nation- states.
Includes bibliographical references.
Keywords: POLITICAL SCIENCE -- PHILIPPINES